A COMMUNITY JUST FOR PRACTICE: A CASE OF AN INCLUSIVE/SPECIAL EDUCATION COURSE - Thompson, S. (Canadian Journal of Education/Revue canadienne de l'éducation, 2007)
Using a reflective case‐study methodology, I conducted an innovative method in my inclusive/special education course, informed by the Communities of Practice literature and interprofessional collaboration. The student participants, in groups, accomplished an assignment designed to support a learner with a disability/exceptionality by including in their plans relevant professionals and community stakeholders. Data consisted of tape‐recorded focus group interviews and group planning meetings, as well as two researcher journals. Two themes emerged: the status of members of a community of practice affected group leadership, and to work effectively, promoting interprofessional collaboration within a university course should account for communities of practice already established in the field. Key words: community of practice; inclusive/special teacher education Dans le cadre d’une étude de cas réflexive, l’auteur a introduit dans un cours de formation à l’enseignement inclusif et d’orthopédagogie une méthode novatrice intégrant la littérature des communautés de praticiens et la collaboration interprofessionnelle. En petits groupes, les étudiants avaient un devoir dont le but était d’établir un plan qui incluait des professionnels et des parties prenantes dans la communauté pour aider un apprenant ayant une déficience. Des enregistrements réalisés lors de groupes de discussion, des réunions de planification en groupe et les journaux de bord de deux chercheurs ont permis de réunir les données nécessaires à cette étude. Deux thèmes ont émergé : le statut des membres d’une communauté de praticiens a affecté le leadership dans le groupe et, pour assurer un travail efficace, la promotion de la collaboration interprofessionnelle à l’intérieur d’un cours universitaire devrait tenir compte des communautés de praticiens déjà établies dans le domaine. Mots clés: communauté de praticiens, formation à l’enseignement inclusive, orthopédagogie